Fabrication and functionalization of biocompatible carboxymethyl chitosan/gelatin membranes via anodic electrophoretic deposition. Issue 9 (16th February 2022) - Wang, Fushi; Qiao, Weiwei; Guo, Weiting; Li, Zhiwen; Cai, Xinjie
Abstract : A biocompatible CMC/G membrane for titanium substrates has been fabricated in an eco-friendly manner and could be a promising carrier for negatively charged agents. Abstract : Peri-implant surgical site infection is a significant challenge in oral implant surgery. Numerous surface functionalization methods, including electrophoretic deposition, have been studied to functionalize implant surfaces to prevent peri-implantitis. However, it is still challenging to load anti-inflammatory agents having negative charges into electrophoretic deposition membranes. The present study aimed to use water-soluble chitosan derivatives to fabricate negatively charged carboxymethyl chitosan/gelatin (CMCG) composite membranes on titanium (Ti) substrates via anodic electrophoretic deposition (AED). Membranes incorporating different amounts of gelatin were labeled as CMC, CMCG4, CMCG6, and CMCG8. X-ray diffraction and Fourier transform infrared spectroscopy tests verified that CMCG could be deposited on Ti disks via AED. The result of the contact angle test showed that groups incorporating gelatin had a certain degree of hydrophobicity. After rehydration, the membranes swelled by approximately 200% in weight. Fluorescence microscopy and scanning electron microscopy images showed that bone marrow stromal cells (BMSCs) on membranes stretched well, showing a good cell adhesion ability. The CCK-8 test demonstrated that CMCG6 had the highest proliferation rate. Cell apoptosis studies showed that CMCG could inhibit apoptosis of BMSCs statistically. It suggests that the CMCG membrane fabricated by AED would be a potent candidate for surface functionalization of biomaterials with negative charges.